Surgical Management of External Hydrocephalus in a Calf - Vahora, Mohsin S.; Patel, Sanjay B.; Shukla, Preeti G. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Hydrocephalus is an accumulation of excessive fluid in dura matter or ventricles of the brain thereby leading to the swelling of the cranium (Long, 2001). Congenital hydrocephalus can be internal or external, and is mainly due to abnormal development of the foetus during pregnancy; however, hereditary, infectious, environmental and nutritional factors can also predispose this condition (Whitlock et al., 2008). This condition has been reported occasionally in the ewe, doe, mare, and sow, whilst it is rarely seen in cattle and buffalo (Long, 2001; Sharda and Ingole, 2002; Dhami et al., 2007; Saini et al., 2019). Hydrocephalus occurs mainly due to three reasons, as excessive production of cerebrospinal fluid (CSF), defective absorption of CSF, and interference in the passage of CSF. Hydrocephalus may cause increased intracranial cerebral pressure, progressive enlargement of the head, convulsions, mental disability, and even death (Mausumi et al. 2014.).